Asuhan Keperawatan Anestesiologi pada Pasien Otitis Media Supuratif Kronis Dilakukan Timpanoplasti dengan General Anestesi Intubasi di Kamar Operasi RSUD Arosuka Kabupaten Solok - Rahmiwati Aprian; Made Suandika; Thopan Heri Wibowo (Pusat Riset dan Inovasi Nasional, 2025)
Chronic Suppurative Otitis Media (CSOM) is a middle ear disease characterized by tympanic membrane perforation and persistent ear discharge, often leading to hearing loss and a higher risk of severe complications. The management of CSOM through tympanoplasty requires comprehensive anesthetic care to ensure patient safety and comfort. This case study aims to describe the anesthesiology nursing care for CSOM patients undergoing tympanoplasty with general anesthesia and intubation. A qualitative case study approach was applied to five patients at RSUD Arosuka, Solok Regency, covering the stages of assessment, identification of anesthetic health problems, interventions, implementation, and evaluation. The findings indicated that although the patients were generally fit for surgery, potential anesthetic problems were identified, including preoperative anxiety, difficult intubation, respiratory and cardiovascular risks, thermoregulation disorders, delayed recovery, fall risk, and postoperative shivering. All interventions were systematically carried out based on evidence-based practice, successfully preventing complications and supporting optimal recovery. This study emphasizes the critical role of nurse anesthetists, not only in technical skills but also in risk detection, patient education, and collaborative care. Comprehensive, planned, and evidence-based anesthetic nursing care proved effective in maintaining perioperative stability and improving surgical safety outcomes for tympanoplasty patients.